PH-operated hybrid silica nanoparticles with multiple H-bond stoppers for colon cancer therapy1. Issue 80 (2nd September 2015) - Théron, C.; Gallud, A.; Giret, S.; Maynadier, M.; Grégoire, D.; Puche, P.; Jacquet, E.; Pop, G.; Sgarbura, O.; Bellet, V.; Hibner, U.; Zink, J. I.; et al.
<x xml:space="preserve">Abstract</x> Controlled delivery of a chemotherapeutic drug from pH-sensitive hybrid silica nanocarriers efficiently targets colon carcinoma cells. The drug, blocked by cyanuric acid as stopper, is autonomously released inside the cancer cells.